The import dependency of the automotive sector in Turkey (2000-2018) - Aydemir, Tuğçe (My University, 2021)
While Turkey is included in the global value chain accompanied by globalization and vertical specialization, Turkey's foreign trade volume has been increasing year by year. Export is a significant driver in terms of economic growth and development. Turkey, which is located in the World's top 20 largest countries, aims to reach export target of 500 billion dollars in 2023. However, the value-added of exported commodities that provide, has been continuing to decrease until last a few years gradually. Turkey is one of the most important commercial vehicle producers in Europe. Undoubtedly, the reasons of Turkey's attraction are that Turkey stays on an important geographical position and its population. Despite increasing automobile production and market share within years, increase in export of automobile starts to create less value-added due to using of imported inputs. Although this situation follows a fluctuating course, it reflects a general trend. Import dependence of Turkey is mentioned with a sectoral perspective in this study. Firstly, the foreign trade of Turkey is interpreted with the help of 1980-2018 data. After that, as mentioned above, automotive sector, which plays a key role in Turkish Economy as an example sector, is discussed. The data of UN Comtrade, TUIK and Automotive Manufacturers Association is obtained to analyze sectoral. The sector is a key sector due to the fact that it creates business districts in other sectors and it is also the top export sector in Turkey after 2003. In the last part of the study, the automotive sector, which attains such a substantial success, the import dependency of the sector is exhibited and it is aimed to draw attention to the problems that is created from this case. Moreover, this study is mentioned about some short suggestions.

Küreselleşen dünyada Türkiye, dikey uzmanlaşmanın eşlik ettiği bir küresel değer zincirine dahil olurken, dış ticaret hacmi de her geçen yıl artmaktadır. İhracat, ekonomik büyüme ve gelişme açısından önemli bir itici güçtür. Dünyanın ilk 20 büyük ülkesi içinde yer alan Türkiye'nin amacı 2023 yılında 500 milyar dolarlık ihracat hedefine ulaşmak olmasına rağmen, ihraç edilen mallardan elde edilen katma değer son birkaç yılda azalma seyri göstermektedir. Avrupa'nın en önemli ticari araç üreticilerinden biri olan Türkiye’nin bir cazibe merkezi olmasının nedenlerinden biri hiç şüphesiz ülkenin coğrafi konumu, bir diğer nedeni ise nüfusudur. Yıllar içinde artan otomobil üretimi ve pazar payına rağmen otomobil ihracatındaki artış, ithal girdilerinin kullanılması nedeniyle daha az katma değer yaratmaya başlamıştır. Bu durum zaman içinde dalgalı bir seyir izlese de genel bir trendi göstermektedir. Bu çalışmada, Türkiye'nin ithalata olan bu bağımlılığından sektörel bir bakış açısıyla söz edilmiştir. Bu çalışmada önce Türkiye’nin dış ticareti kısaca 1980-2010 verilerin yardımıyla yorumlanmış, ardından örnek sektör olarak, Türkiye ihracatında yukarıda da bahsettiğimiz gibi önemli bir rol oynayan otomotiv sektörü ele alınmıştır. Sektörel analiz yapabilmek için UN Comtrade, TÜİK ve Otomobil Sanayii Derneği’nin verilerinden yararlanılmıştır. Sektör, diğer sektörlerde iş bölgeleri yaratması nedeniyle kilit bir konumdadır ve aynı zamanda 2003 yılından sonra Türkiye'nin en büyük ihracat sektörüdür. Çalışmanın son kısmında, ihracatta bu denli önemli bir başarı elde eden sektörün ithalata olan bağımlılığını ortaya koyarken, bunun yaratacağı problemlere dikkat çekilmek istenmekte, ayrıca bazı kısa önerilere değinilmektedir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2021
Keywords: İthal bağımlılık; Otomotiv aksam ve parçaları; Küresel değer zinciri; Dikey uzmanlaşma; Karşılıklı bağımlılık; Import dependency; Automotive parts & components; Global value chain; Vertical specialization; Intra-industry trade